Toward Developing Chemical Modulators of Hsp60 as Potential Therapeutics - Meng, Qianli; Li, Bingbing X.; Xiao, Xiangshu (Frontiers in Molecular Biosciences, 2018)
The 60 kDa heat shock protein (Hsp60) is classically known as a mitochondrial chaperonin protein working together with co-chaperonin 10 kDa heat shock protein (Hsp10). This chaperonin complex is essential for folding proteins newly imported into mitochondria. However, Hsp60 and/or Hsp10 have also been shown to reside in other subcellular compartments including extracellular space, cytosol and nucleus. The proteins in these extra-mitochondrial compartments may possess a wide range of functions dependent or independent of its chaperoning activity. But the mechanistic details remain unknown. Mutations in Hsp60 gene have been shown to be associated with neurodegenerative disorders. Abnormality in expression level and/or subcellular localization have also been detected from different diseased tissues including inflammatory diseases and various cancers. Therefore, there is a strong interest in developing small molecule modulators of Hsp60. Most of the reported inhibitors were discovered through various chemoproteomics strategies. In this review, we will describe the recent progress in this area with reported inhibitors from both natural products and synthetic compounds. The former includes mizoribine, epolactaene, myrtucommulone, stephacidin B and avrainvillamide while the latter includes o-carboranylphenoxyacetanilide and gold (III) porphyrins. The potencies of the known inhibitors range from low micromolar to millimolar concentrations. The potential applications of these inhibitors include anti-cancer, anti-inflammatory diseases and anti-autoimmune diseases.